Desarrollo de actividades prácticas dirigidas a la adquisición de competencias profesionales - Reyes-Iglesias, Pedro José; Garrido-Balsells, José María (My University, 2018)
Most companies require engineering graduates with transversal skills, in addition to technical competences, for their professional practice. Therefore, regional, national and European engineering accreditation agencies pay special attention to the adequate development and assessment of transversal skills at university degrees. Programming practical activities to develop simultaneously transversal and technical skills in last year compulsory subjects is highly desirable for the imminent Degree Final Project (TFG). In this paper we describe the implementation of such practical activity and the achievement of the objectives according to the results and students feedback.
Keywords: Ingeniería - Enseñanza; Docencia; Ingeniería; Competencias transversales; Actividades prácticas